(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The purpose of this paper is to examine the impact of a museum’s website design on visitors’ intentions. Three hypotheses were set which assume that the design of a museum website has a positive influence on the intention of visitors to return to the website, to personally visit the museum, and to recommend the website to their friends and relatives. To achieve the purpose of the research, empirical research was carried out. The respondents evaluated the websites of 145 Croatian museums and responded to questions which indicate their intention of revisiting the website, personally visiting the museums and recommending the website to other people. The hypotheses are tested and confirmed using the partial least squares structural equation modelling (PLS-SEM). This research confirmed the perception of the website design to be a significant predictor of visitors’ intentions regarding website revisits and of visiting the museums personally. Research results have also confirmed a significant and positive impact of visitors’ assessment of a museum website and their intentions to recommend the website to others. The results of this research contribute to the theory and practice. Interpretation and generalization of the findings should be taken with caution because this study used a convenient sample of university students, which does not represent the entire population of museum website users. The research model represents a novelty in the current research studies, since it contains a new dimension “Overall impression” which has the most effect on the positive evaluation of the website. Keywords: Museum marketing, web marketing, website, PLS